ORAL HYGIENE BURUK PASIEN RAWAT INAP TIDAK BERKAITAN DENGAN PERTUMBUHAN ORAL CANDIDIASIS - Addina Aimana Sabila; Ade Ismail A.K; Rochman Mujayanto (ODONTO : Dental Journal, 2017)
Background: Nosocomial infections can develop in the oral cavity due to poor oral hygiene. Oral Candidiasis is one of the most frequent nosocomial infection in oral cavity. The objective of this study is to describe the oral hygiene and oral candidiasis in hospitalized patients. Method: This analitical observational study used cross sectional design. Subject of the study were 74 adult patients aged 20-65 who are hospitalized at the Sultan Agung Islamic Hospital Semarang. Oral hygiene assessed from the presence of debris and calculus on the tooth surface using Simplified Oral Hygiene Index (OHIS) that were grouped in three categories (good, moderate, bad). Oral candidiasis diagnosed through clinical examination and swab procedure of suspicious lesions, and identified the presence of its spores and hyphae under a microscope observation. Kendal Tau test is used to analyze the correlation between oral hygiene with oral candidiasis. Results: Results showed patients with oral candidiasis in the poor and moderate oral hygiene were 29.7% and 1.4%, whereas patients without oral candidiasis in the poor and moderate oral hygiene were 60.8% and 8.1%. Kendall Tau correlation test results p value of 0.235 (p> 0.05). Conclusion: Conclusion of this study showed there is no association between oral hygiene with oral candidiasis.